A Collective Strategy in Digital Zakat Collection by Dompet Dhuafa via E-Commerce - Fachmi, Fany Aulia; Fatwa, Nur (Indonesian Journal of Multidisciplinary Science, 2023)
Zakat collection is a form of charitable giving that has attracted a lot of attention in recent years. However, zakat collection in Indonesia has undergone a transformation from traditional to digital. This study aims to analyze the collective strategy that is carried out by Dompet Dhuafa digitally through e-commerce as an effort to realize the potential of the digital economy in Indonesia. This research uses qualitative research with a case study approach or case studies that examines a particular case in a real contemporary context or setting. The data is analyzed by reading and reviewing the data (observation notes, interview transcripts) to identify emerging themes and patterns. In general, it appears that digital donations have a significant impact on zakat collection. In addition, it is hoped that this research can become a reference for further research that wants to discuss digital zacat collection.